Microorganisms (Staphylococcus and Fungi) in Radiotherapy Patient Masks before and after Cleaning with Disinfectant Liquid - Dartini Dartini; Mahalul Azam; Evi Widowati; Dina Nur Anggraini Ningrum; Fatimah Fatimah; Jeffri Ardiyanto (International Conference on Science, Education, and Technology, 2023)
Background: Radiotherapy masks patients are a fixation tool in radiotherapy radiation services. The function of the radiotherapy mask is to fix the irradiation area in the patient’s body part for serial radiation therapy, for approximately 1 month. A printed radiotherapy mask is used by the patient from the first session until the final session of radiation is complete. The inner surface of the mask is always in contact with the patient's skin. Practically, the masks are never been cleaned so it is possible to develop infectious Fungi or microorganisms. The research objective was to determine the difference in the number of microorganisms (Staphylococcus and Fungi) before and after cleaning using a 70% alcohol disinfectant Methodology: This is experimental research. The number of microorganisms (Staphylococcus and Fungi) in 16 radiotherapy masks were identified with the Swap method before and after cleaning using 70% alcohol disinfectant. Data were analyzed using the Wilcoxon test to determine the differences in the number of microorganisms before and after cleaning and to identify the reduction percentages. Result: the number of Fungi and Staphylococcus before cleaning were 9,528 and 0.490, while after cleaning were 8228 and 0,194, respectively The amount of percentage reductions before and after cleaning were 43.275% (Staphylococcus ) and 38.529% (Fungi). Based on the Wilcoxon test on Staphylococcus , meaning that. There was a difference in Staphylococcus (ρ value= 0.003) on the radiotherapy patient's mask before and after cleaning using 70% alcohol. There was no difference in Fungi (ρ value= 0.220) before and after being cleaned using 70% alcohol. The research results are very important as material for the revision of standard operational procedures for radiotherapy services.